1983
DOI: 10.3382/ps.0621080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Population Density on the Growth, Organ Weights, and Plasma Corticosterone of Young Broiler Chicks

Abstract: Two trials were conducted with broiler chicks to determine the effects of population density on the growth, feed efficiency, and several physiological parameters associated with stress in birds. Chicks were brooded in batteries at 116, 232, 348, and 697 cm2/chick. Chicks brooded at 348 cm2/chick grew and utilized feed significantly better than those brooded at 697 cm2/chick during the first week. For maximum growth and feed efficiency, 116 cm2/chick was adequate for the first week; 232 cm2/chick was adequate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
3
1
4
Order By: Relevance
“…Our results are similar to those of Pesti and Howarth (1983), but are different from the results of Dozier et al (2006), Ravindran et al (2006), and Onbasilar et al (2008) in that no effect of stocking density was reported (Dozier et al, 2006;Ravindran et al, 2006) and a decrease in feed intake was observed (Dozier et al, 2006;Onbasilar et al, 2008). Literature on young birds is scarce because the majority of studies deal with the whole rear-ing period or the last period of rearing.…”
Section: Effect Of Stocking Density On Young Broilers (1 To 3 Wk Old)contrasting
confidence: 73%
“…Our results are similar to those of Pesti and Howarth (1983), but are different from the results of Dozier et al (2006), Ravindran et al (2006), and Onbasilar et al (2008) in that no effect of stocking density was reported (Dozier et al, 2006;Ravindran et al, 2006) and a decrease in feed intake was observed (Dozier et al, 2006;Onbasilar et al, 2008). Literature on young birds is scarce because the majority of studies deal with the whole rear-ing period or the last period of rearing.…”
Section: Effect Of Stocking Density On Young Broilers (1 To 3 Wk Old)contrasting
confidence: 73%
“…Akyuvar sayısında (P<O,05, P<O,OI), lenfosit, heterofil ve Hi L oranlarında (P<O,OI) ilk iki grupla (i ve II) üçüncü ve dördüncü gruplar (II1ve IV) arasında istatistiksel önemde farklar gözlenmiş-tir. Literatürde akyuvar sayısının oluşturulan stres şartlarında değişmediğini (17, 18), azaldığını (20), arttığını (7,14,17) belirten araştırıcılar, azalmayı, oluşan lökopeniye (20) artışı da heterofilIerin oranındaki artışa (7) bağlamaktadırlar. Araştınnamızda akyuvar sayısında bulunan artış kronik streste heterofil sayısının artmasının en duyarlı hematopoetik belirti olduğunu bildiren (7) araştınnaya benzerlik göstennektedir.…”
Section: Tartışma Ve Sonuçunclassified
“…Yetiştiriciler üretim maliyetini düşürebilmek için az yakıt kuııanma durumunda olduklarından, hayvanları sıklaştırmak yoluyla yakıt tasarrufu sağlamak da mümkündür (17).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…닭에서 급성감염에 따른 반응은 다양한 지표를 분석하여 그 스트레스 정도를 조사할 수 있는 데, 지금까지 연구에 따르면, 혈액 생화학적 성상의 변화, 백 혈구 수, 스트레스 호르몬, 항체, 사이토카인 등과 같은 것들 이 급성 스트레스 단계에서 발현 지표들로 알려져 있다 (Koj 1996;Kaiser et al, 2009;Leshchinsky and Klasing, 2003;Mireles et al, 2005;Pesti and Howarth, 1983). 특히 친염증 및 항염증 사이토카인의 발현 정도가 급성감염지표로서 최근 많 은 연구가 진행되고 있다 (Shini et al, 2010).…”
unclassified